Management of Liquid Medical Waste in some General Health Centers in Lattakia Governorate - لمى جرعا (Latakia University Journal -Engineering Sciences Series, 2022)
The problem of pollution in its various forms is global, from which everyone suffers. Pollution with medical waste is one of the most important of these problems. Medical waste is caused by health care institutions, and it has been divided globally into several types. We discussed this statistical study of how to manage medical waste that takes a liquid form when disposed of in some general health centers in Lattakia Governorate. It was found that there is a lack of knowledge of how to distinguish between medical waste, especially liquid ones, which led to errors in its classification, and thus led to its access to natural resources as a result of these errors. Therefore, it is necessary to rehabilitate and train health sector workers to use the globally used methods to deal with them, and to raise awareness of them and their risks.